Genetic types and accumulation models of natural gas in the Weixinan depression of the Beibu Gulf Basin in the western South China Sea - Desheng Hu; Gang Zhou; Xinde Xu; Junjun You (Natural Gas Industry B)
Exploration in the Weixinan depression of the Beibu Gulf Basin has long focused on crude oil, with less natural gas exploration, so the genetic types and accumulation characteristics of the natural gas in the depression have not been determined. Therefore, this study explored the geochemical characteristics, origins and sources, filling periods, and migration and accumulation models of natural gas in the Weixinan depression of the Beibu Gulf Basin, based on data on natural gas composition, light hydrocarbon composition, stable carbon isotopes, and fluid inclusions. The results showed that the natural gas in the Weixinan depression is mainly composed of hydrocarbon gases, with methane (CH4) predominating (62 %–96 %, with an average of 78 %). The percentage of heavy hydrocarbon gases (C2-5) is high (average 20 %), and the drying coefficient (C1/C1-5) is generally less than 0.95, indicative of typical wet gas. The carbon isotope ratios of methane (δ13C1) range from −51.60 ‰ to −34.37 ‰, and the carbon isotope ratios of ethane (δ13C2) range from −36.67 ‰ to −16.53 ‰, respectively. The carbon isotopes of alkane gases generally show a positive sequence distribution, and a degree of carbon isotopic reversal in natural gas occurs in some well areas. It is speculated that the carbon isotope reversal may be related to the mixing of natural gas from multiple sets of source rocks in the same stage or from the same set of source rocks in different stages. The natural gas is mainly oil-type gas, probably originating from the oil shale in the lower sub-member of the second member of the Liushagang Formation (E2l2l), with some contributions from the shale in the upper sub-member of the third member of the Liushagang Formation (E2l3u). The study area has seen multiple periods of oil and gas filling. The area away from the sub-sags experienced a single, early period of natural gas filling associated with mature crude oil generated during the same period. However, in the zone near the sub-sags, there have been multiple relatively long periods of continuous natural gas filling. Two migration and accumulation models are developed: indirect natural gas filling with no contact between the source rocks and the reservoirs in the zone away from the sub-sags, and continuous natural gas filling with the source rocks in direct contact with the reservoirs in the zone near the sub-sags. The results revealed the genetic types and reservoir characteristics of the natural gas in the Weixinan depression, which is crucial for decision-making for the next step of natural gas exploration.